One new species of Homogryllacris Liu, 2007 from China with comments on the characters of mitochondrial genome (Orthoptera: Gryllacrididae; Gryllacridini) - Liu, Jing; Lu, Xiangyi; Bian, Xun (Zootaxa, 2021)
This paper reported on new species from China which differs from other species of Homogryllacris in being without styli of male subgenital plate. The nearly complete mitochondrial genome (mitogenome), except control region, of the new species Homogryllacris parcibrevipenna was sequenced and analyzed. This partial mitogenome was 15509 bp in length and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA unit genes. The gene arrangement and contents were consistent with other members of the Gryllacrididae. All the PCGs were started with the standard ATN codons except ND1 with TTG; and most of PCGs were terminated with a complete stop codon (TAA/TAG). Most tRNAs could be folded into the typical cloverleaf secondary structures, while tRNASer1 lacked a DHU stem. This data could enrich the genome information available for Gryllacrididae and facilitate phylogenetic studies of related insects. All the material were deposited in the Museum of Guangxi Normal University.